Joel, Obadiah, Malachi - Baker, David Weston, 1950- (Grand Rapids, MI Zondervan, 2006)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Joel -- commentaries; Bible. O.T. Obadiah -- commentaries; Bible. O.T. Malachi -- commentaries